2013
DOI: 10.4028/www.scientific.net/amr.772.480
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Thermal Performance of Flat Plate Heat Pipe with Intersected Micro-Grooves

Abstract: A copper-water flat plate heat pipe with intersected micro-grooves was developed for cooling electronic devices in this paper. The effects of heat flux, working fluid filling ratio and inclination angles on thermal performance of the flat plate heat pipe was tested and investigated. The laboratory tests show the optimal filling ratio of the heat pipe is about 65%. Excellent thermal performance is also observed in unfavorable titled positions including vertical and anti-gravity orientation at 65%. The smallest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the past two decades, many scholars have made and studied FHPs with different structures, sizes, and materials [16][17][18][19][20][21][22][23]. Table 1 shows summarization of the researchers study about FHPs and their performances of devices.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, many scholars have made and studied FHPs with different structures, sizes, and materials [16][17][18][19][20][21][22][23]. Table 1 shows summarization of the researchers study about FHPs and their performances of devices.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the previous researches, a number of studies regarding the design and performance evaluation of FHPs have also flourished lately . A review of the related literatures indicates that FHPs can spread heat rapidly and have the advantages of compactness and lightness. However, flat heat pipes for special applications, such as the application in multiple possible configurations where the heat sink may be out of plane with heat source , are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the related literatures [6,7,[15][16][17][18][19][20][21] indicates that FHPs can spread heat rapidly and have the advantages of compactness and lightness. However, flat heat pipes for special applications, such as the application in multiple possible configurations where the heat sink may be out of plane with heat source [22], are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…B. Mathew et al 8 reported a MEMS-based capillary heat exchanger for thermal harvesting; heat transfer tests were carried out and the results showed that the MEMS-based phase-change operations were comparable with or better than those of single-phase microchannel heat sinks. Chen Wang et al 9 14 performed a thermo-hydraulic study of fluid in open micro-channels etched in the inner surface of externally heated horizontal pipes containing two-phase flow from theory and experiments. MEMSbased MHPs are not similar to the MHPs shown above.…”
Section: Introductionmentioning
confidence: 99%